Assessing the Effectiveness and Efficiency of the Public Service Budget - Dendy Syaiful Akbar; Irfan Faris Rudiana; Benny Prawiranegara; Mira Aryanti (Jurnal Ilmiah Akuntansi Kesatuan, 2022)
Public services by local governments will not be separated from the use of the budget. The budget must be used effectively and efficiently so that it is expected to improve services to the community on an ongoing basis. This research was conducted in one area in Indonesia, namely in Ciamis Regency. The purpose of this study was to assess the effectiveness and efficiency of the public service budget in the local government of the Ciamis Regency. The research method used is a descriptive method with a quantitative approach. The level of effectiveness is measured by comparing the target with the realization of the public service budget. The public service budget is one component of regional expenditure. Meanwhile, the level of efficiency is measured by comparing the public service budget with regional expenditures. The results showed that most of the public service budget has been used effectively and very efficiently.